Investigating Teachers' Assessment Practices: Exploratory, Non-Foundationalist, Mixed-Method Research - Shulha, Lyn M.; Wilson, Robert J.; Anderson, John O. (Alberta Journal of Educational Research, 1999)
Audiences for educational research are rarely invited to review the decision-making processes that permeate systematic inquiry. This account of three researchers' efforts to make sense of preservice teachers' assessment practices reveals how methodologically diverse investigations emanated from the context of a single study. The developments, findings, and warrants that characterize this inquiry are presented, as well as arguments why in retrospect this study can be described as exploratory, mixed-method, non-foundationalist research. Consistent with the general themes of pragmatism, the reader is invited to subject the account of novice teachers' assessment practices to intense scrutiny and to judge the success of the researchers' efforts to build at least temporary certainty and primacy for claims about novice teachers' thinking and behavior. The same process can also be used with the suggested consequences for classroom assessment practice, which conclude both this article and the series.